2014
DOI: 10.1371/journal.pone.0088769
|View full text |Cite
|
Sign up to set email alerts
|

Stenotrophomonas maltophilia Virulence and Specific Variations in Trace Elements during Acute Lung Infection: Implications in Cystic Fibrosis

Abstract: Metal ions are necessary for the proper functioning of the immune system, and, therefore, they might have a significant influence on the interaction between bacteria and host. Ionic dyshomeostasis has been recently observed also in cystic fibrosis (CF) patients, whose respiratory tract is frequently colonized by Stenotrophomonas maltophilia. For the first time, here we used an inductively mass spectrometry method to perform a spatial and temporal analysis of the pattern of changes in a broad range of major tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…Recently, it was found that Stenotrophomonas maltophilia, a bacterium in the family Xanthomonadeaceae associated with cystic fibrosis in humans, modifies the host lung ionome in a virulence-dependent fashion (Pompilio et al 2014), suggesting that this phenomenon could be widespread. Recently, it was found that Stenotrophomonas maltophilia, a bacterium in the family Xanthomonadeaceae associated with cystic fibrosis in humans, modifies the host lung ionome in a virulence-dependent fashion (Pompilio et al 2014), suggesting that this phenomenon could be widespread.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that Stenotrophomonas maltophilia, a bacterium in the family Xanthomonadeaceae associated with cystic fibrosis in humans, modifies the host lung ionome in a virulence-dependent fashion (Pompilio et al 2014), suggesting that this phenomenon could be widespread. Recently, it was found that Stenotrophomonas maltophilia, a bacterium in the family Xanthomonadeaceae associated with cystic fibrosis in humans, modifies the host lung ionome in a virulence-dependent fashion (Pompilio et al 2014), suggesting that this phenomenon could be widespread.…”
Section: Discussionmentioning
confidence: 99%
“…The increased levels of Fe and Mg in LPS and LA+LPS groups might be associated with the simultaneous decrease of these elements in the lung and other tissues. The existence of E.coli-mediated lipid peroxidation in peritoneum has been detected; and this is accompanied by an increase in Cu, Fe and Zn levels (25). Another study has found that induced sepsis by cecal ligation and sepsis have significantly reduced levels of Zn and Cu in all tissues (22).…”
Section: Discussionmentioning
confidence: 99%
“…During bacterial infection, liver and kidney Mn levels are further decreased, suggesting the existence of additional global mechanisms that starve microbes during inflammation. Notably, the host proteins responsible for this redistribution of Mn during infection have not been identified Pompilio et al, 2014). Second, the host possesses mechanisms to restrict Mn within the intracellular phagosomal compartment as well as in the extracellular environment.…”
Section: Bacterial Response To Mn Restriction During Infectionmentioning
confidence: 99%